6ER-016 Analysis of prescribed treatments for patients with pulmonary hypertension in a provincial hospital. (2nd March 2018) - Olivar, L Enríquez; Martin, A Muñoz; García, E Queipo; González-Aller, J Varela; Mñoz, S Izquierdo; Pariente, A; Ramis, F
Abstract : Background: Pulmonary hypertension (PH) is a chronic disease with a high mortality rate. Therefore, choosing the right treatment at the right time is essential. Purpose: To analyse which treatments were prescribed depending on the type of disease and to analyse the treatment results and adverse effects on patients in a provincial hospital. Material and methods: Retrospective and observational study of every active patients with PH from 20 February 2002 until 1 April 2017 in the outpatients' programme. The following variables were collected: age, sex, PH type according to ESC/ERC-2015 guide, first treatment and its date, change of treatment and reason, first and last functional class, and days of treatment until 1 April 2017. Data were extracted from the archives of the hospital pharmacy service, collected in an Excel table and analysed. Results: Fifty-eight patients were included: 36% (21/58)were males and 64% (37/58) were females with an average age of 69±20.4 years. The average duration of the treatment was 1, 720 days (4 years and 9 months). 91.4% (53/58) patients initiated monotherapy: 39.6% (21/53) with bosentan, 32.1% (17/53) with sildenafilo, 20.8% (11/53) with ambrisentan, 5.6% (3/53) with iloprost and 1.9% (1/53) with tadalafilo. 8.6% (5/58) patients initiated combination therapy: 40% (2/5) with tadalafilo +ambrisentan, 20% (2/5) with sildenafilo +ambrisentan, 20% (2/5) with sildenafilo +iloprost and 20% (2/5) with ambrisentan +iloprost. Nowadays: 67.2% (39/58) patients are in monotherapy: 38.5% (15/39) with sildenafilo, 28.2% (11/39) with bosentan, 25.6% (10/39) with ambrisentan, 5.1% (2/39) with tadalafilo, 2.6% (1/39) with iloprost. 20.7% (12/58) patients in combination therapy: 25% (3/12) with tadalafilo+ambrisentan, 16.7% (2/12) with sildenafilo+ambrisentan, 16.7% (2/12) with tadalafilo+iloprost, 16.7% (2/12) with tadalafilo+bosentan, 8.3% (1/12) with sildenafilo+bosentan, 8.3% (1/12) with sildenafilo+iloprost, 8.3% (1/12) with macitentan+iloprost. 12.1% (7/58) patients in triple therapy: 42.8% (3/7) with tadalafilo+bosentan+teprostinil, 28.6% (2/7) with tadalafilo+ambrisentan+iloprost, 14.3% (1/7) with tadalafilo+bosentan+iloprost, 14.3% (1/7) with sildenafilo+bosentan+teprostinil. Sixty-four changes of treatment occurred: 48.4% (31/64) were due to disease progression and 51.6% (33/64) due to adverse reactions. In the group of adverse reactions: 27.3% (9/33) were patients treated with sildenafilo, mainly oedema; 27.3% (9/33) with ambrisentan, mainly oedema; 27.3% (9/33) with bosentan, mainly intolerance; 6.1% (2/33) with tadalafilo, migraine and oedema; 6.1% (2/33) with sitaxentan, liver toxicity; 3% (1/33) with iloprost, oedema; and 3% (1/33) with macitentan intolerance. Conclusion: Recommendations from the ESC/ERC-2015 were followed at our hospital, based on sequential combination therapy: 91.4% patients started with monotherapy, mostly endothelin–receptor–antagonists. Later, if it was necessary, a second drug was added, a phosphodiesterase–5–inhibitor. If expected results were not achieved, or if patients' conditions worsened, a third drug was added, being the main triple therapy completed with a prostaciclyn–analogous. References and/or Acknowledgements: Sociedad Europea de Cardiologia (ESC) y la European Respiratory Society (ERS) 2015. Evaluación–diagnóstica–y–pronóstica–actual–de–la–hipertensión–pulmonar. No conflict of interest